METODE PARENTING PROPHETIC DALAM MEMBANGUN AKHLAK MULIA - Wawan Setiawan; Rizky Putri Amalia; Eful Saefullah Nurul Fahmi (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
Morals are a reflection of an attitude in a person that has an important influence on various aspects of life, this is the reason why the cultivation of noble morals must be done from an early age. Prophetic parenting is considered the right method for mothers in the Al-Ihsan taklim assembly who act as madrasatul ula, to instill noble character in their children from an early age. This study aims to find out how the process of applying prophetic parenting to build noble character in the Al-Ihsan taklim assembly. This research method uses a qualitative descriptive method with a phenomenological approach and uses a persuasive paradigm. The results of this study indicate that the parenting method of prophetic communication carried out by mothers at the Al-Ihsan taklim assembly is applying simple things both verbally and nonverbally, namely daily activities carried out by children such as giving instructions, giving examples well, feeding, clothing, etc., which of course is based on the morals or behavior of the prophet Muhammad SAW. Parents are a good example for their children, so in giving any good instructions it is appropriate to set a good example or role model as well. One of the good instructions given by mothers at the Al-Ihsan Taklim assembly is to instill honesty. Furthermore, in communicating and giving good directions, the mothers in the Al-Ihsan taklim assembly chose the right time to give these instructions. Because choosing the right time is also one of the things that must be considered, because it also has an influence on the child's acceptance when instructions or directions are given.